THE DEVELOPMENT PROCESS OF A CHILD’S SELF-CONCEPTION AND MOTIVATION AREA - O’risheva, Pokiza (Журнал Педагогики и психологии в современном образовании, 2022)
In this article, the pre-school education system is further improved as an important link of the integrated continuous education system, and modern educational programs and technologies that develop children intellectually, spiritually, aesthetically and physically are introduced into the educational process. In order to radically increase the level of their school readiness, the process of development of the child’s self-awareness and motivational sphere, as well as emotion and its development, are described.